2017
DOI: 10.1038/s41467-017-00991-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of genomic and epigenomic regulation of the transcriptome in liver cancer

Abstract: Hepatocellular carcinoma harbors numerous genomic and epigenomic aberrations of DNA copy numbers and DNA methylation. Transcriptomic deregulation by these aberrations plays key driver roles in heterogeneous progression of cancers. Here, we profile DNA copy numbers, DNA methylation, and messenger RNA expression levels from 64 cases of hepatocellular carcinoma specimens. We find that the frequencies of the aberrancies of the DNA copy-number-correlated (CNVcor) expression genes and the methylation-correlated expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 43 publications
10
82
0
Order By: Relevance
“…It was reported that 17q25.1‐3 copy number gain was a prognostic marker for poor patient survival in HCC . In liver cancer, the methylation‐correlated expression genes and DNA copy number‐correlated expression genes are significantly co‐regulated . We then explored the methylation status and copy number of DNAH17 in our cohort and noted that a lower methylation level of HCC samples was observed in DNAH17 amplification patients compared with the rest patients, which consisted with the data from TCGA data set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that 17q25.1‐3 copy number gain was a prognostic marker for poor patient survival in HCC . In liver cancer, the methylation‐correlated expression genes and DNA copy number‐correlated expression genes are significantly co‐regulated . We then explored the methylation status and copy number of DNAH17 in our cohort and noted that a lower methylation level of HCC samples was observed in DNAH17 amplification patients compared with the rest patients, which consisted with the data from TCGA data set.…”
Section: Discussionmentioning
confidence: 99%
“…27 In liver cancer, the methylation-correlated expression genes and DNA copy number-correlated expression genes are significantly co-regulated. 5 We then explored the methylation status and copy number of DNAH17 in our cohort and noted that a lower methylation level of HCC samples was observed in DNAH17 amplification patients compared with the rest patients, which consisted with the data from TCGA data set. This finding indicated that the DNAH17 overexpression in HCC tissue was possibly regulated by the synergy of gene amplification and hypomethylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilayered genomic and epigenomic aberrations of these genes could identify three molecular subtypes. One of the subtypes was characterized by recurrent mutation of BAP1 , which is frequently mutated in iCCA, and concomitant expression of stem cell–like traits such as CA‐9 and KRT19 . These studies, along with the TCGA study, consistently suggest that the common features of HCC and iCCA play critical roles in acquisition of the aggressive HCC phenotype, linking their resemblance with bipotential stem cells that can differentiate into hepatocytes as well as cholangiocytes.…”
mentioning
confidence: 84%
“…In a study by Woo et al, DNA copy-number variation, methylation and gene expression were profiled in a cohort of hepatocellular carcinoma (HCC) patients. Integrative omics analysis revealed three molecular subtypes of HCC with differences in prognostic outcomes (5). Zhu et al performed a comprehensive pan-cancer integrative analysis showing that a combination of clinical variables with molecular profiles improves prognostic power in 7 of the 14 cancer types studied (6).…”
Section: Introductionmentioning
confidence: 99%